Augmented Reality in 4D Flashcard: The Effects in Teaching Speaking Skill - Nanning Nanning; Ismail Latif; Putri Nasrinda; Ahmed Sardi (JELITA, 2024)
The use of augmented reality of 4D flashcard is one of the media that supports teaching English, especially in speaking skills, it can also increase students' confidence and interest in learning. The purpose of this study was to determine whether the use of augmented reality in 4D flashcard can improve students ' speaking skills. This study used a pre-experimental method with one group pre-test and post-test design. The sample of this study was Class XI MIPA 3 consisting of 34 people with classroom random sampling techniques. This research instrument was a test of speaking skills. The results of this study showed that there was an increase in the students’ average score. The pre-test score of students (55.37) is greater than the post-test (71.03). In the significance level p (5%) and T-test value of 2.03 is greater than T-table 16.46 (2.03 ° 16.46). Thus, it can be concluded that the use of augmented reality of 4D flashcard students were able to improve students’ speaking skills. So, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted.